2019
DOI: 10.1111/add.14641
|View full text |Cite
|
Sign up to set email alerts
|

Using wastewater‐based analysis to monitor the effects of legalized retail sales on cannabis consumption in Washington State, USA

Abstract: AimsTo perform a wastewater‐based analysis to explore the impact of newly legalized retail cannabis sales on its use and to determine if this approach could estimate the size of the legal market place, which began 1 August 2014 in the study area.DesignLaboratory study of raw wastewater samples collected and analyzed over the 3‐year period from 2014 to 2016.Setting and ParticipantsSamples obtained from the two wastewater treatment plants that serviced a municipality of 200 000 people in the state of Washington,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Studies of the Washington market have found increased use over time after adult use legalization. A study utilizing analyses of raw wastewater sample from 2014 to 2016 found evidence of increasing use in 2016, consistent with survey results (Burgard et al 2019 ). A study utilizing the Behavioral Risk Factor Surveillance System survey for Washington found increased use and frequent use after legalization to be associated with access to retail stores, rather than legalization or store opening generally (Everson et al 2019 ).…”
Section: Introductionsupporting
confidence: 77%
“…Studies of the Washington market have found increased use over time after adult use legalization. A study utilizing analyses of raw wastewater sample from 2014 to 2016 found evidence of increasing use in 2016, consistent with survey results (Burgard et al 2019 ). A study utilizing the Behavioral Risk Factor Surveillance System survey for Washington found increased use and frequent use after legalization to be associated with access to retail stores, rather than legalization or store opening generally (Everson et al 2019 ).…”
Section: Introductionsupporting
confidence: 77%
“…Additionally, population surveys are expensive and complex to perform ( Hernández et al, 2018 ). The benefits of WBE resulted in the publication of studies in many countries of the world ( Archer et al, 2018 ; Bannwarth et al, 2019 ; Banta-Green et al, 2016 ; Bartelt-Hunt et al, 2009 ; Baz-Lomba et al, 2016 ; Benaglia et al, 2020 ; Boleda et al, 2009 ; Burgard et al, 2019 ; Foppe et al, 2018 ; Kankaanpää et al, 2016 ; Mackulˇak et al, 2014 ; Maldaner et al, 2012 ; Metcalfe et al, 2010 ; van Nuijs et al, 2009b ; Zhang et al, 2019 ; Zuccato et al, 2008 ). In fact, since 2011, the Europe-wide network (Sewage analysis CORe Group Europe (SCORE)) performs the systematic monitoring of consumption biomarkers of four priority drugs (cocaine, methylenedioxymethamphetamine (MDMA), amphetamine, and methamphetamine) in WWTPs, covering 68 cities from 23 European countries in 2019 ( EMCDDA, 2020 ).…”
Section: Wastewater-based Epidemiologymentioning
confidence: 99%
“…Specifically, if an increase was observed WBE cannot distinguish between the following possibilities i) more individuals are consuming at the same rate, ii) slightly more individuals consuming and at a higher rate each, iii) the same number of individuals consuming a higher total amount each, or iv) one group of individuals in the cohort consuming more than another group. Nevertheless, wastewater samples can be analyzed retrospectively to provide aggregated consumption estimates (Boogaerts et al, 2016;Burgard et al, 2019;Mackie et al, 2019) with easily adjusted spatio-temporal frequencies and short time-lags in gathering and reporting data. While specific socio-demographic features of individuals might not easily be obtained, WBE can provide a spatial comparison between different populations with different socio-economic status at a community level (P. Choi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%